AN ANALYSIS OF ANXIETIES THAT EXPERIENCED BY MARLIN AS THE MAIN CHARACTER IN FINDING NEMO (2003) FILM - Novi Nur Cahyati; Idha Nur Hamidah (Jurnal Ilmiah Sultan Agung, 2022)
This study analyzes the anxieties experienced by Marlin as the main character in Finding Nemo (2003) film by using Sigmund Freud’s anxiety theory. The method uses in this study is descriptive qualitative. The data are taken from the film, such as dialogues, narration, and monologues. The step uses to collect data, such as watching film and reading film script, identifying data, and classifying data. The result of this study is Marlin, as the main character in Finding Nemo (2003) film, has anxiety due to Nemo being taken away by divers. Marlin has two anxieties according to Sigmund Freud's theory, namely realistic anxiety and neurotic anxiety.